Evaluation of Cinnamon Essential Oil and Its Emulsion on Biofilm-Associated Components of Acinetobacter baumannii Clinical Strains - Tea Ganić; Ilinka Pećinar; Biljana Nikolić; Dušan Kekić; Nina Tomić; Stefana Cvetković; Stefana Vuletić; Dragana Mitić-Ćulafić (Antibiotics)
Background/Objectives: Acinetobacter baumannii, one of the most dangerous pathogens, is able to form biofilm structures and aggravate its treatment. For that reason, new antibiofilm agents are in need, and new sources of antibiofilm compounds are being sought from plants and their products. Cinnamon essential oil is associated with a wide spectrum of biological activities, but with a further improvement of its physicochemical properties it could provide even better bioavailability. The aim of this work was the evaluation of the antibiofilm properties of cinnamon essential oil and its emulsion. Methods: In order to evaluate the antibiofilm activity, crystal violet assay was performed to determine biofilm biomass. The main components of the biofilm matrix were measured as well as the motile capacity of the tested strains. Gene expression was monitored with RT-qPCR, while treated biofilms were observed with Raman spectroscopy. Results: A particularly strong potential against pre-formed biofilm with a decreased biomass of up to 66% was found. The effect was monitored not only with regard to the whole biofilm biomass, but also on the individual components of the biofilm matrix such as exopolysaccharides, proteins, and eDNA molecules. Protein share drops in treated biofilms demonstrated the most consistency among strains and rose to 75%. The changes in strain motility and gene expressions were investigated after the treatments were carried out. Raman spectroscopy revealed the influence of the studied compounds on chemical bond types and the components present in the biofilm matrix of the tested strains. Conclusions: The results obtained from this research are promising regarding cinnamon essential oil and its emulsion as potential antibiofilm agents, so further investigation of their activity is encouraged for their potential use in biomedical applications.